During the COVID-19 pandemic, home learning assistance can boost student interest - Usmiyatun U; Niken Dwi Safitri (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
The closure of educational institutions is often regarded as a highly effective measure in mitigating the transmission of the COVID-19 virus. Distance learning is being implemented in light of the current circumstances and the perceived vulnerability to the transmission of the COVID-19 virus. The objective of this essay is to elucidate the favorable reception of students in Pasuruan towards the home learning aid program. Home learning assistance refers to providing guidance and support inside the home environment to aid students in overcoming challenges encountered during the learning process. The research employed the descriptive survey method as its chosen methodology. The focus of the learning aid program is on pupils at the elementary and middle school levels. The pupils must complete a questionnaire to receive feedback on the learning support program. The findings indicate that the learning support program was well-received by pupils in Pasuruan. Providing learning aids has been found to enhance students' motivation to learn. This is attributed to the alleviation of students' workload and the perception of increased understanding, which is reinforced by the involvement of fellow students who offer exceptional and fun support. During the ongoing COVID-19 epidemic, there has been an observed increase in students' enthusiasm for the process of learning.